2000
DOI: 10.1016/s1388-9842(00)00091-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different methods of functional evaluation in patients with chronic heart failure

Abstract: Background: Stratification of the severity of heart failure has major prognostic and therapeutic implications. Aims: To Ž . prospectively compare different methods of assessment of functional capacity in patients with chronic heart failure CHF . Ž . Ž . Methods and results:We studied 143 patients 78 male and 65 female with CHF aged less than 70 years mean 57.3 years . Functional assessment was made clinically according to NYHA classification and according to the Goldman Activity Scale Ž . Ž . Classification GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 34 publications
4
44
0
3
Order By: Relevance
“…19 Our results confirm the limitations of clinical evaluation of functional class in a chronic disease. Rostagno et al 20 showed in his study of chronic heart failure patients that concordance between NYHA classification and levels of performance using cardiopulmonary exercise testing was Ͻ50%. Our study shows that subjective evaluation of functional class underestimates the cardiovascular burden of the left-to-right shunt.…”
Section: Discussionmentioning
confidence: 99%
“…19 Our results confirm the limitations of clinical evaluation of functional class in a chronic disease. Rostagno et al 20 showed in his study of chronic heart failure patients that concordance between NYHA classification and levels of performance using cardiopulmonary exercise testing was Ͻ50%. Our study shows that subjective evaluation of functional class underestimates the cardiovascular burden of the left-to-right shunt.…”
Section: Discussionmentioning
confidence: 99%
“…Overall Jehn et al 50 Radke et al 24 Alahdab et al 18 Alahdab et al 18 Rostagno et al 13 Rostagno et al 45 Ingle et al 26 Jehn et al 36 Ingle et al 26 Deuschle et al 52 Rostagno et al 46 Bagur et al 48 Zugck et al 21 Pepera et al 32 Goode et al 18 Deuschle et al 52 Faggiano et al 47 Leszek et al 35 Rostagno et al 13 Goode et al 7 Zugck et al 21 Ingle et al 26 Ingle et al 26 Rostagno et al 45 Tay et al 49 Jankowska et al 29 Bagur et al 48 Ates et al 30 Rostagno et al 46 Gary et al 25 Jehn et al 36 Karavidaset al 28 Souza et al 53 Jehn et al 50 Bosnak Güçlü et al 27 Alahdab et al 18 Forman et al 20 Zaidi et al Goscinska-Bis et al 37 Alahdab et al 18 Forman et al 20 Keast et al 31 Vrtovec et al 51 Rostagno et al 45 Souza et al 53 Tay et al 49 Jaski et al 34 Zugck et al …”
Section: Discussionmentioning
confidence: 99%
“…The exertional fatigue exhibited in patients with HF has been attributed to underperfusion of skeletal muscle because patients with HF on average demonstrate reduced cardiac output and leg blood flow responses to exercise (23,(27)(28)(29)(31)(32)(33)(34)(35)(36). Patients with HF and exertional fatigue were, however, shown to be limited by skeletal muscle abnormalities rather than by skeletal muscle underperfusion (35).…”
Section: Discussionmentioning
confidence: 99%